2011
DOI: 10.1016/j.visres.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The context effect in face matching: Effects of feedback

Abstract: Faces are perceived holistically, even when they are presented briefly (Hole, 1994; Richler, Mack, et al., 2009). Results obtained with a context congruency paradigm support dominance of holistic processing for brief timings, but indicate that larger viewing times enable observers to regulate contextual influences, and to use a feature selective focus (Meinhardt-Injac, Persike, & Meinhardt, 2010). Here we provide further evidence for this claim, and illuminate the role of feedback. With trial by trial feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…However, Meinhardt-Injac et al (2011) reported this function of feedback in controlling the contextual effects of external features on internal target features. There, subjects were able to use feedback for improvement in incongruent trials, while performance in congruent trials remained as good as that in the without feedback condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Meinhardt-Injac et al (2011) reported this function of feedback in controlling the contextual effects of external features on internal target features. There, subjects were able to use feedback for improvement in incongruent trials, while performance in congruent trials remained as good as that in the without feedback condition.…”
Section: Discussionmentioning
confidence: 99%
“…To make the perceptual account of the composite effect more explicit, one may conceive an ideal “holistic” observer who refers to a whole face as the smallest perceptual unit when exposed to natural and intact face stimuli. However, this notion is just an ideal, because human observers can take a part-based focus of facial stimuli (Meinhardt-Injac et al, 2010, 2011). As outlined above, this observer would yield a large congruency effect in the complete design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing different age groups, our aim was to tap into the improvement of the visual processing ability for faces and watches as common non-face visual objects that share complexity and structure with faces [13]. For all age groups, the context congruency paradigm was employed as the experimental task [8], [9], [13]. Participants were required to judge internal features of two faces/watches as same or different, while ignoring the identity of the external features.…”
Section: Introductionmentioning
confidence: 99%
“…In this paradigm, the effects of context congruency (for short referred to as “context effect” – see also Methods Section) and orientation were used as measures of holistic and configural face processing, respectively. Variation of exposure duration provided hints on the strength of holistic and configural viewing at different processing stages [8], [9].…”
Section: Introductionmentioning
confidence: 99%